2019
DOI: 10.1136/bmjopen-2019-029555
|View full text |Cite
|
Sign up to set email alerts
|

Arts for ageing well: a propensity score matching analysis of the effects of arts engagements on holistic well-being among older Asian adults above 50 years of age

Abstract: ObjectiveTo assess the frequency and intensity of arts engagement inclusive of active and passive engagements in arts, culture and heritage activities among Singaporean adults aged 50 and above, and examine the relationships between participatory art and holistic well-being.DesignCross-sectional stratified household survey.SettingAll residential areas across Singapore’s Central, East, North, North-East and West Regions.Participants1067 community-dwelling, Singaporean older adults between the ages of 50 and 95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The results show a similar pattern for both diseases examined in this study, implying that both diabetes and hypertension prevalence peak among middle-aged individuals (around age 60 years). Consistent with previous studies, this study showed that the effect of age on diabetes is nearly logarithmic with respect to respondent age [ 61 , 62 ]. Moreover, the study on the prevalence and associated factors of hypertension in a national sample of older South Africans who participated in the Study of Global Ageing and Adults’ Health found high rates of hypertension among older adults (50 years and more) in South Africa [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results show a similar pattern for both diseases examined in this study, implying that both diabetes and hypertension prevalence peak among middle-aged individuals (around age 60 years). Consistent with previous studies, this study showed that the effect of age on diabetes is nearly logarithmic with respect to respondent age [ 61 , 62 ]. Moreover, the study on the prevalence and associated factors of hypertension in a national sample of older South Africans who participated in the Study of Global Ageing and Adults’ Health found high rates of hypertension among older adults (50 years and more) in South Africa [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, quality of life has been examined in relation to participation in numerous artistic disciplines, such as music, dance, theatre, literature and visual arts. A better quality of life was found in those who actively participate (Ho et al 2019 ). Studies on participation in artistic activities highlight the benefits to well-being (Reynolds 2010 ), including spiritual well-being (Ho et al 2019 ; Tzanidaki and Reynolds 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, no previous studies have used propensity score matching to investigate associations between participation in arts groups and wellbeing in older adults. Studies using similar methods in younger adults have found inconsistent evidence for the association between arts engagement and wellbeing, which is likely a result of the measures of arts engagement used, as well as differences in follow-up periods (23,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, even after adjusting for potential confounders, residual imbalance between those who do and do not engage in the arts can still bias results (30). Some studies have employed more sophisticated methods to address this, such as fixed effects regression and propensity score matching, but have not found consistent evidence for the association between arts engagement and wellbeing in younger adults (23,31,32). There are very few studies of these associations specifically in older adults (2022).…”
Section: Introductionmentioning
confidence: 99%